Basic problems in the system of education the Republic of Kazakhstan. (Journal of Economic Research & Business Administration, 2016)
The last 10 years in Kazakhstan there are significant changes not only in the socio-political sphere. And one of them is – a sphere of education. Whatever I did not have time care and education of young generation is the most important, responsible work. Therefore, education is greatly influenced by changes and innovations in the way to the improvement and development of the country. There is a need to drive for a worldwide area of education, to new situations in the development of society, the problems that have arisen out of nowhere, comes into the world educational area. The current goal of the educational system – training of personnel capable of competitively. From this point of view, Kazakhstan’s strategy in the field of education and science is determined entry into the world educational space, while preserving the national education and the idea of education in the education system. Particularly important is to update the content of education by ensuring that the optimal ratio of programs at different levels of education. In general, the organization of training-Trial waiting for changes in the form of transition from strictly standardi.
Keywords: education; primary education; higher education; doctorate.